Agreement of Sleep Measures—A Comparison between a Sleep Diary and Three Consumer Wearable Devices - Kristina Klier; Matthias Wagner (Sensors, 2022)
Nowadays, self-tracking and optimization are widely spread. As sleep is essential for well-being, health, and peak performance, the number of available consumer technologies to assess individual sleep behavior is increasing rapidly. However, little is known about the consumer wearables’ usability and reliability for sleep tracking. Therefore, the aim of the present study was to compare the sleep measures of wearable devices with a standardized sleep diary in young healthy adults in free-living conditions. We tracked night sleep from 30 participants (19 females, 11 males; 24.3 ± 4.2 years old). Each wore three wearables and simultaneously assessed individual sleep patterns for four consecutive nights. Wearables and diaries correlated substantially regarding time in bed (Range CCCLin: 0.74–0.84) and total sleep time (Range CCCLin: 0.76–0.85). There was no sufficient agreement regarding the measures of sleep efficiency (Range CCCLin: 0.05–0.34) and sleep interruptions (Range CCCLin: −0.02–0.10). Finally, these results show wearables to be an easy-to-handle, time- and cost-efficient alternative to tracking sleep in healthy populations. Future research should develop and empirically test the usability of such consumer sleep technologies.